From ratings to discourse: Gen Z and film evaluation on rating platforms in Indonesia - Dimas Ramadhiansyah; Danang Jaya Arganata; Deo Agung Sembada (Universitas Indraprasta PGRI, 2026)
Although film rating and review platforms, alongside social media, have rapidly expanded among Generation Z, most existing research examines these platforms in isolation. Consequently, there is limited understanding of their combined influence on contemporary film evaluation practices. This study addresses this gap by investigating how Gen Z audiences in Indonesia engage with these platforms as part of an interconnected digital ecosystem that shapes film selection, evaluation, and cultural participation. Employing a qualitative-descriptive methodology, the study utilizes semi-structured, in-depth interviews with six purposively sampled Gen Z informants who actively use film rating and review platforms (such as IMDb, Letterboxd, and Rotten Tomatoes) and social media. Thematic analysis was conducted to identify recurring patterns in platform use, evaluation practices, and social interaction. Technological determinism serves as the primary analytical framework, further refined by the concept of digital dialectic, which highlights the reciprocal relationship between technological structures and user agency. The findings indicate that film rating and review platforms function not only as evaluative tools but also as social spaces where ratings, reviews, and algorithmic recommendations intersect with social media discourse, collectively shaping evaluation practices. Gen Z audiences are positioned as active participants who negotiate technological affordances while reinforcing platform-driven logics of simplification and visibility. This study contributes to media and film studies by illustrating how platform infrastructures and user practices operate dialectically, transforming film criticism into a participatory and algorithmically mediated cultural practice.